GPCRs in rat primary skeletal muscle cells - Haddad, Mansour Emil Goerge (2012)
GPCRs are the largest family of proteins in the human genome and a target for huge numbers of therapeutic drugs. However, the role of skeletal muscle in the action of these drugs is unclear. Given the unique importance of GPCR signalling in terms of glucose and fatty acid turnover in other tissues, it would be anticipated that GPCR identified to influence metabolism in these tissues might well be expressed in skeletal muscle. This study investigated the expression of genes encoding GPCRs in skeletal muscle and in cultured preparations thereof. In particular, this study focussed on the expression and signalling of adenosine receptors, a2-adrenoceptor, P2Y receptors and CBI cannabinoid receptors and the impact of CBI receptor modulation upon insulin signalling in rat primary skeletal muscle cells. All experiments in this work looked at GPCR expression and their signalling; with either tissues or cultured cells from rats. These experiments included: 1. Transcriptional profiling of skeletal muscle tissue in Wistar rats for GPCRs and proteins in associated signalling pathways. 2. Signalling of GPCRs (adenosine, a2A-adrenoceptor, P2y) in rat primary skeletal muscle cells. 3. Cannabinoid signalling pathways and cross-talk with insulin signalling. 4. CBI cannabinoid receptor antagonist/inverse agonist/agonist treatment of rat primary skeletal muscle cells. Expression of example members of the three major G protein coupling GPCR families was observed in rat skeletal muscle tissue. mRNA encoding Gs- (A2Aadenosine receptor, P2-adrenoceptor), Gi- (AI adenosine receptor, (l2A-adrenoceptor), and Gq-coupled (P2Y 1. P2Y2 and P2Y6 receptors) receptors were detected using gene microarray (Agilent, all ranked <10220 out of 41090). QRT-PCR (Taqman) identified (l2A-adrenoceptor and CBI cannabinoid receptor mRNA expression at low level similar across myoblasts, myotubes and skeletal muscle tissue. Functional responses to example members of the three major G protein coupling families of GPCR were also observed in rat primary skeletal muscle preparations. First, treatment of myotubes with the non-selective adenosine receptor agonist NECA elicited increases in cAMP, which were inhibited in the presence of the A2Badenosine receptorselective antagonist, PSB603. In contrast, the A2A-selective agonist, CGS21680 failed to evoke a significant cAMP elevation in myotubes. Second, neither basal nor forskolinevoked elevation of cAMP was altered in the presence of the Ar-selective agonist, SENBA. Third, the (l2-adrenoceptor agonist UK14304 inhibited forskolin-evoked cAMP levels, however, rauwolscine did not prevent this effect. Treatment with UK14304 also increased phosphorylation of ERK1/2; these responses, however, were inhibited by rauwolscine. In addition, rauwolscine in the absence of other ligands also inhibited ERK phosphorylation. Fourth, ATP and UTP, P2Y receptor agonists, elevated intracellular calcium ion levels in myoblasts. Although expression of mRNA for CBI cannabinoid receptors was detected in myoblasts, myotubes and skeletal muscle tissue, forskolin-evoked elevation of cAMP was unaltered in the presence of the CBI receptor-selective agonist ACEA or the antagonist/inverse agonist rimonabant in cultured myotubes. AICAR-stimulated AMPactivated protein kinase activity was also unaltered by ACEA. However, treatment with ACEA increased activation ofERK1I2 and p38 mitogen-activated protein kinases; these responses were significantly inhibited by rimonabant. Insulin treatment of myotubes increased the activation (phosphorylation) of AKT/protein kinase B, glycogen synthase kinase 3(1 and ~, ERK1I2 and p38 MAP kinases; however, pre-treatment with ACEA for 24 hours failed to alter these responses. In conclusion, these studies indicate expression and functional responses to select members of the three major G protein coupling families of GPCR in rat skeletal muscle preparations. These findings also provided evidence for expression of functionally active CB) cannabinoid receptors in skeletal muscle. However, they fail to support previous reports suggesting an interaction between insulin and CB) receptor signalling in these cells. The impact of CB) receptor function in skeletal muscle should be the subject of further investigation.